Pelatihan Ecoprint sebagai Media Edukasi dan Inovasi Ramah Lingkungan bagi Remaja Putri Nagari Bintungan Padang Pariaman - Widdiyanti Widdiyanti; Yulimarni Yulimarni; Anin Ditto; Yuliarni Yuliarni; Hijratur Rahmi (Lembaga Pengembangan Kinerja Dosen, 2025)
The community service program activities that have been carried out are related to ecoprint techniques, which involve printing using natural materials such as leaves, flowers, and plant stems to produce patterns or motifs on fabric media. This training activity aims to enhance the knowledge and skills of the young girls in Bintungan Nagari, so they can be creative and innovative through ecoprint techniques. It provides knowledge and broadens their understanding of how to utilize the natural potential available in the environment around Bintungan Nagari. This training also aims to create environmentally friendly products to foster a healthy and clean environment. The hope for this activity is to have a positive impact on improving the knowledge and skills of young girls as the generation that brings about change. The training uses an approach of counseling, demonstration, training, and mentoring, along with evaluation. The results of the training program indicate a high level of enthusiasm from the participants, with knowledge and skills acquired, they have been able to produce sheets of fabric with unique motifs from the ecoprint technique. This has opened up space for participants to generate new ideas and create interesting motif patterns from natural materials. The products produced not only serve as a medium of expression but also have the potential to be developed as environmentally friendly, local creative products.